Fibroblasts in intestinal homeostasis, damage, and repair - Chalkidi, Niki; Paraskeva, Christina; Koliaraki, Vasiliki (Frontiers in Immunology, 2022)
The mammalian intestine is a self-renewing tissue that ensures nutrient absorption while acting as a barrier against environmental insults. This is achieved by mature intestinal epithelial cells, the renewing capacity of intestinal stem cells at the base of the crypts, the development of immune tolerance, and the regulatory functions of stromal cells. Upon intestinal injury or inflammation, this tightly regulated mucosal homeostasis is disrupted and is followed by a series of events that lead to tissue repair and the restoration of organ function. It is now well established that fibroblasts play significant roles both in the maintenance of epithelial and immune homeostasis in the intestine and the response to tissue damage mainly through the secretion of a variety of soluble mediators and ligands and the remodeling of the extracellular matrix. In addition, recent advances in single-cell transcriptomics have revealed an unexpected heterogeneity of fibroblasts that comprise distinct cell subsets in normal and inflammatory conditions, indicative of diverse functions. However, there is still little consensus on the number, terminology, and functional properties of these subsets. Moreover, it is still unclear how individual fibroblast subsets can regulate intestinal repair processes and what is their impact on the pathogenesis of inflammatory bowel disease. In this mini-review, we aim to provide a concise overview of recent advances in the field, that we believe will help clarify current concepts on fibroblast heterogeneity and functions and advance our understanding of the contribution of fibroblasts in intestinal damage and repair.